DNA methylation alterations in muscle of critically ill patients. Issue 3 (11th March 2022) - Van Dyck, Lisa; Güiza, Fabian; Derese, Inge; Pauwels, Lies; Casaer, Michaël P.; Hermans, Greet; Wouters, Pieter J.; Van den Berghe, Greet; Vanhorebeek, Ilse
Abstract: Background: Intensive care unit (ICU)‐acquired weakness can persist beyond ICU stay and has been associated with long‐term functional impairment of ICU survivors. Recently, DNA methylation alterations were found in the blood of ICU patients, partially explaining long‐term developmental impairment of critically ill children. As illness‐induced aberrant DNA methylation theoretically could also be involved in long‐term weakness, we investigated whether the DNA methylation signature in muscle of adult critically ill patients differs from that in muscle of healthy controls. Methods: Genome‐wide methylation was determined (Infinium® HumanMethylationEPIC BeadChips) in DNA extracted from skeletal muscle biopsies that had been collected on Day 8 ± 1 in ICU from 172 EPaNIC‐trial patients [66% male sex, median age 62.7 years, median body mass index (BMI) 25.9 kg/m 2 ] and 20 matched healthy controls (70% male sex, median age 58.0 years, median BMI 24.4 kg/m 2 ). Methylation status of individual cytosine–phosphate–guanine (CpG) sites of patients and controls was compared with F ‐tests, using the Benjamini–Hochberg false discovery rate to correct for multiple comparisons. Differential methylation of DNA regions was assessed with bump hunting, with 1000 permutations assessing uncertainty, expressed as family‐wise error rate. Gene expression was investigated for 10 representative affected genes. Results: In DNA from ICU patients, 565 CpG sites, associated with 400 unique genes, were differentially methylated as compared with controls (average difference 3.2 ± 0.1% ranging up to 16.9%, P < 0.00005). Many of the associated genes appeared highly relevant for muscle structure and function/weakness, including genes involved in myogenesis, muscle regeneration, nerve/muscle membrane excitability, muscle denervation/re‐innervation, axon guidance/myelination/degeneration/regeneration, synapse function, ion channelling with especially calcium signalling, metabolism (glucose, protein, and fat), insulin signalling, neuroendocrine hormone regulation, mitochondrial function, autophagy, apoptosis, oxidative stress, Wnt signalling, transcription regulation, muscle fat infiltration during regeneration, and fibrosis. In patients as compared with controls, we also identified two hypomethylated regions, spanning 18 and 3 CpG sites in the promoters of the HIC1 and NADK2 genes, respectively (average differences 5.8 ± 0.01% and 12.1 ± 0.04%, family‐wise error rate <0.05). HIC1 and NADK2 play important roles in muscle regeneration and postsynaptic acetylcholine receptors and in mitochondrial processes, respectively. Nine of 10 investigated genes containing DNA methylation alterations were differentially expressed in patients as compared with controls ( P ≤ 0.03). Conclusions: Critically ill patients present with a different DNA methylation signature in skeletal muscle as compared with healthy controls, which in theory could provide a biological basis for long‐term persistence of weakness in ICU survivors. Trial registration: ClinicalTrials.gov: NCT00512122, registered on 31 July 2007.